2020
DOI: 10.1186/s12947-020-00207-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of a novel automated three-dimensional ultrasonographic analysis system for abdominal aortic aneurysm: comparison with two-dimensional ultrasonography and computed tomography

Abstract: Background: Accurate measurement of the maximum aortic diameter (Dmax) is crucial for patients with abdominal aortic aneurysm (AAA). Aortic computed tomography (CT) provides accurate Dmax values by threedimensional (3-D) reconstruction but may cause nephrotoxicity because of contrast use and radiation hazard. We aimed to evaluate the accuracy of a novel semi-automated 3-D ultrasonography (3-D US) system compared with that of CT as a reference. Methods: Patients with AAA (n = 59) or individuals with normal aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…By implementing 3D-US in the decision process, a five-fold decrease in the risk of underestimating the AAA size was observed. Previous studies comparing 3D-US and 2D-US diameter assessment with CTA have already shown superior agreement between 3D-US and CTA in native AAA, 13,18,22 and the 3Dderived dual-plane technique implemented as standard US-modality for AAA surveillance in our J o u r n a l P r e -p r o o f clinic, has shown to minimise the operator variability and improve agreement with CTA 13 . Nevertheless, other centers, using conventional 2D-US, might experience an even greater difference between US and CTA diameter, than evident in the current study, which furtherly advocates a future shift from 2D to 3D imaging.…”
Section: Discussionmentioning
confidence: 82%
“…By implementing 3D-US in the decision process, a five-fold decrease in the risk of underestimating the AAA size was observed. Previous studies comparing 3D-US and 2D-US diameter assessment with CTA have already shown superior agreement between 3D-US and CTA in native AAA, 13,18,22 and the 3Dderived dual-plane technique implemented as standard US-modality for AAA surveillance in our J o u r n a l P r e -p r o o f clinic, has shown to minimise the operator variability and improve agreement with CTA 13 . Nevertheless, other centers, using conventional 2D-US, might experience an even greater difference between US and CTA diameter, than evident in the current study, which furtherly advocates a future shift from 2D to 3D imaging.…”
Section: Discussionmentioning
confidence: 82%
“…14 , 15 Segmentation and analysis of CTA, as well as registration with segmentation of 4D-US imaging, were performed by three independent investigators. We have not proven the interobserver variability of single examinations, 16 reliability of the segmentation process, and value of the averaged models for 4D-US, 14 , 15 , 17 as well as the reliability of the segmentation of the geometry and stress analysis for CTA 18 once again, because these processes have already been published and classified as reliable. However, we registered the conformity of AAA geometry in the 4D-US and in the gold standard CTA as the absolute prerequisite for the comparative analysis of wall strain and wall stress.…”
Section: Methodsmentioning
confidence: 90%
“…CT-A is considered a gold standard for geometry reconstructions mainly because it is a suitable tool for imaging the entire aneurysm and accurately measuring AAA size with high reproducibility (Cho et al. 2020 ) and has been established in the past as a suitable means for measuring and detecting AAA growth (diameter and volume) with high accuracy and reproducibility (Bargellini et al. 2005 ; Kauffmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also 3D ultrasound could be found to be a suitable method to determine maximal diameter, vessel area as well as vessel and thrombus volume with excellent agreement compared to CT imaging (Cho et al. 2020 ). The median Hausdorff Distance found here between the US and CT-A geometries of 5.1 [4.5, 6.1] mm is in good agreement with 4.6 [4.0, 5.9] mm from van Disseldorp et al.…”
Section: Discussionmentioning
confidence: 99%